Respuesta :

Answer:

1. 0

2. 0

3. 0

Step-by-step explanation:

6x + 18 = 3(2x + 7) - 3

open the brackets by using 3 to multiply the bracket behind it

6x + 18 = 6x + 21

collect like terms. when + crosses = sign it changes to -

6x - 6x = 21 - 18 - 3

0 = 21 - 21

0

4(0.5a + 3) = 2a + 12

multiply contents of the bracket with 4

2a + 12 = 2a + 12

collect like terms. when + crosses = sign it changes to -

2a - 2a = 12 - 12

0

x + 4 - 6x = 6 - 5x - 2

collect like terms. when + crosses = sign it changes to -

x + 5x - x = 6 - 4 - 2

6x - 6x = 6 - 6

0

Answer:

The correct answer's B, give brainly if this helped :)

Step-by-step explanation:

ACCESS MORE